Myofibrillogenesis regulator 1 (MR-1): a potential therapeutic target for cancer and PNKD. (14th September 2018) - Wang, Junxia; Zhao, Wuli; Liu, Hong; He, Hongwei; Shao, Rongguang
Abstract: Human myofibrillogenesis regulator 1 ( MR-1 ) is a functional gene also known as paroxysmal nonkinesigenic dyskinesia (PNKD). It is localised on human chromosome 2q35 and three different isomers, MR-1L, MR-1M and MR-1S, are formed by alternative splicing. MR-1S promotes cardiac hypertrophy and is closely related to cancer. MR-1S is overexpressed in haematologic and solid malignancies, such as hepatoma, breast cancer and chronic myelogenous leukaemia. MR-1S causes disordered cell differentiation, initiates malignant transformation and accelerates metastasis. MR-1S directly phosphorylates and activates the MEK-ERK-RSK pathway to accelerate cancer growth and facilitates metastasis by activating the MLC2-FAK-AKT pathway. Silencing MR-1 inhibits cancer cell proliferation and metastasis. MR-1S causes disordered cell differentiation, initiates malignant transformation and accelerates metastasis. MR-1 interacts with eukaryotic translation initiation factors and MRIP-1, which contains Ras GTPase, PH and zinc-containing ArfGap domains, as well as three ankyrin repeats. Mutations in the N-terminal region of MR-1L and MR-1S are the main causes of PNKD (a hereditary disease characterised by paroxysmal dystonic choreoathetosis) and targeting the mutated protein could provide symptomatic relief. These findings provide compelling evidence that MR-1 might be a diagnostic marker and therapeutic target for solid tumours, myelogenous leukaemia and PNKD.